Repatriation Adaptation Strategy Surinamean Java in Tongar Village Nagari Aia Gadang West Pasaman - Rizki Aditiya; Mutia Kahanna; Hijratur Rahmi (Kirana Publisher (KNPub), 2024)
This research discusses the adaptation strategy of Javanese Surinamese repatriates in Tongar Nagari Aia Gadang Village, West Pasaman. The aim of this research is to describe the initial obstacles faced by Javanese Surinamese repatriates in Tongar Village and to describe the adaptation strategies of Javanese Surinamese repatriates in Tongar village. This research method used is qualitative research. Data collection techniques are field observations, interviews and documentation. The theories used are Michael P. Todaro's migration theory and John W. Bennet's adaptation theory. The findings of this research are that Javanese Surinamese repatriates who were in Tongar Village faced obstacles such as language, economics, land ownership and difficult road access when they came to Tongar, then the repatriants adapted to their new environment by means of cultural adjustments, interaction processes, job options, road repairs. Therefore, these repatriates have their own way of continuing to survive in Tongar Village, they have also started to get used to socializing and are used to their new environment, so that the Javanese Surinamese repatriates can survive to this day in Tongar Village.